Implementation of the Directive 2013/11/EU on Alternative Dispute Resolution for Consumer Disputes – Historical Background and Legal Consequences of a Failure to Transpose the Directive within the Prescribed Time - Magoń, Karol (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The purpose of this article is to undertake a legal analysis of the legal process of implementing Directive 2013/11/EU into the Polish legal order and to present the legal consequences of a failure to transpose the Directive within the prescribed period. In the first part, the author presents the description of work that has been done at the EU level on the alternative resolution of consumer disputes and evaluates the proposals for specific legal solutions presented in the course of this work. The author then presents the main issues and challenges associated with the process of the transposition of Directive 2013/11/EU. In particular, the author reflects on the direct effect of Directive 2013/11/EU, in both vertical and horizontal terms. As a result, the author concludes that the failure to implement the Directive in the prescribed period initiates the State’s liability to an individual for damage caused by the lack of proper implementation and imposes on the national courts the duty of applying a pro-EU interpretation of national law. In turn, in the light of the well-established case law of the CJEU, and given the nature of the analysed Directive, the lack of a proper implementation of Directive 2013/11/EU within the prescribed period, does not entitle the consumer to effectively assert his rights against the trader for non-fulfillment of the obligations resulting from the Directive.